2020
DOI: 10.3389/fpsyg.2020.542326
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Induced Language Modes and Regular Code-Switching Habits Boost Bilinguals’ Executive Performance: Evidence From a Within-Subject Paradigm

Abstract: Bilingualism may modulate executive functions (EFs), but the mechanisms underlying this phenomenon are poorly understood. In this study, we investigated two potential sources of variability in bilinguals' EF performance: (1) interactional contexts and codeswitching, and (2) dominance profiles. Previous research on code-switching often relied on self-reports of regular code-switching habits. In this study, we investigated the effects of experimentally induced language modes (single language versus codeswitching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 80 publications
(207 reference statements)
3
40
0
Order By: Relevance
“…Another goal of our study was to determine whether engagement in different code-switching types (Muysken, 2013) leaves distinct structural signatures on the volumes of the caudate nucleus and thalamus. We based our predictions on the Inhibitory control continuum model and existing empirical studies, which reported that the degree of separation of both languages within a code-switch modulates the cognitive control processes involved (Hofweber et al, 2016(Hofweber et al, , 2020aTreffers-Daller, 2009). Indeed, our results suggest that differences in volumes in the regions of interest are linked to the degree of separation of both languages.…”
Section: Effects Of Frequencies Of Specific Code-switching Typesmentioning
confidence: 89%
“…Another goal of our study was to determine whether engagement in different code-switching types (Muysken, 2013) leaves distinct structural signatures on the volumes of the caudate nucleus and thalamus. We based our predictions on the Inhibitory control continuum model and existing empirical studies, which reported that the degree of separation of both languages within a code-switch modulates the cognitive control processes involved (Hofweber et al, 2016(Hofweber et al, , 2020aTreffers-Daller, 2009). Indeed, our results suggest that differences in volumes in the regions of interest are linked to the degree of separation of both languages.…”
Section: Effects Of Frequencies Of Specific Code-switching Typesmentioning
confidence: 89%
“…One possible account for the finding is that bilingual individuals with varying language dominance patterns engage in different types of code-switching in the Uyghur-Chinese bilingual community, and only those executive functions that are needed to underlie these language practices are impacted. It may be that L1-dominant bilinguals require an effortful suppression of the dominant L1 when they are exposed to the single L2 sociolinguistic context ( Hofweber et al, 2020 ), and this may lead to an improvement in domain-general inhibitory control. However, this is not a full explanation for our finding, because it is known from previous studies that their possibly exclusive language practice of insertional code-switching only recruits a medium level of inhibition, which is lower than what is needed during alternational code-switching ( Treffers-Daller, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of behavioral context is central to many usage-based theories about language and bilingualism, because people perceive and produce the various languages that they know with interlocutors in their environments (such as at home or in the workplace). This rich contextualization of language has wide-ranging consequences for language fluency, processing, representation and control, and it may also carry consequences for domain general cognitive control and underlying brain mechanisms (Adler et al, 2020;Anderson et al, 2018;Beatty-Martinez et al, 2019;Green & Abutalebi, 2013;Grosjean, 2001Grosjean, , 2016Hofweber et al, 2020;Tiv, Gullifer, et al, 2020b). To give one example, the adaptive control hypothesis (Green & Abutalebi, 2013) posits that language usage within particular INTERACTIONAL CONTEXTS will have adaptive consequences for control and brain organization, where interactional contexts consist of the "recurrent pattern of conversational exchanges within a community of speakers" (Green & Abutalebi, 2013, p. 516).…”
Section: Advantages Of Uncertainty Approach To Bilingualismmentioning
confidence: 99%
“…Thus, researchers interested in uncertainty from a cognitive, attention, or decision-making perspective can exploit background language characteristics of participants as a sort of natural experiment. For example, the long-term role of behavioral context in cognitive adaptation can be investigated, between participants, by recruiting and contrasting participants who systematically Downloaded from http://direct.mit.edu/nol/article-pdf/doi/10.1162/nol_a_00044/1927613/nol_a_00044.pdf by guest on 13 July 2021 vary in their language background in terms of interactional context (Beatty-Martinez et al, 2019;Hofweber et al, 2020), providing a sort of naturalistic experiment. Within-participant comparisons can be made through longitudinal studies, for example, by recruiting samples of participants beginning their studies in a new (linguistic) environment and again several months later.…”
Section: Advantages Of Uncertainty Approach To Bilingualismmentioning
confidence: 99%
See 1 more Smart Citation